2009
DOI: 10.1007/s11999-008-0702-9
|View full text |Cite
|
Sign up to set email alerts
|

Gait Analysis after Initial Nonoperative Treatment for Clubfeet: Intermediate Term Followup at Age 5

Abstract: We conducted gait analysis following initial nonoperative clubfoot treatment to compare lower extremity kinematic (eg, ankle motion) and kinetic (eg, ankle power) characteristics between patients treated as infants with Ponseti casting or French physical therapy. This is a followup report of gait characteristics at age 5 years in patients who had previously been tested at age 2 years. One hundred-twenty five clubfeet in 90 patients (34 feet only Ponseti treatment, 40 only French PT, and 51 feet initial nonoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
39
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 31 publications
9
39
1
Order By: Relevance
“…Surgical treatment provides a high percentage of short-term, clinically satisfactory radiological results [3]; however, long-term follow-up results, based on examinations, questionnaires, radiographic analyses [4,5], and kinematics [6], are disappointing. Currently, most physicians agree that extensive soft-tissue release surgeries (joint invasive) should be avoided and that a more conservative, joint-sparing approach should be considered first [5,[7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Surgical treatment provides a high percentage of short-term, clinically satisfactory radiological results [3]; however, long-term follow-up results, based on examinations, questionnaires, radiographic analyses [4,5], and kinematics [6], are disappointing. Currently, most physicians agree that extensive soft-tissue release surgeries (joint invasive) should be avoided and that a more conservative, joint-sparing approach should be considered first [5,[7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Gait analysis following clubfoot treatment has primarily been used in studies involving operatively treated patients [6][7][8][9][10][11][12][13][14][15][16][17][18] ; few have evaluated the Ponseti method in this fashion [19][20][21][22][23][24] . Special foot models allow more detailed evaluation of the foot and of treatment outcomes 11,15,[23][24][25] .…”
mentioning
confidence: 99%
“…While the Achilles tenotomy was not initially included in the protocol, more recent recommendations have been made for correction of residual equinus by gastrocnemius fascial lengthening or heel cord tenotomy as needed in select infants with resistant feet. 3,4 The French technique requires a trained physical therapist and a committed family for success. This program is still in existence in our center as well as in areas of Europe.…”
Section: Physiotherapy Methodsmentioning
confidence: 99%
“…4 El Hawaray et al found that nearly 30% of feet had undergone surgery by the age of 2 years. 3 The gait findings in these patients were not included in the 2008 publication.…”
Section: Clubfoot Gait Analysis Studiesmentioning
confidence: 99%